Seeds of success: seed biology and germination response of Gazania weed in Australia - Adnan, Muhammad; Shahzad, Babar; Collins, Marisa; Bajwa, Ali Ahsan (Frontiers in Agronomy, 2025)
Gazania (Gazania spp.) is a highly invasive plant which is emerging as a difficult-to-control weed in grain production systems and grasslands in southern Australia. Different populations of gazania were compared for their seed morphology and germination response to various environmental factors including temperature, photoperiod, moisture, salinity and pH. Seeds of four populations of gazania were collected from contrasting geographic locations (South Australia and Victoria) and land-use scenarios [roadside (Pop-1), fence line (Pop-2), grain crop production field (Pop-3) and pasture field (Pop-4)] and compared for their seed morphology and germination response to different temperatures and photoperiods. The remaining germination experiments (osmotic potential, salinity and pH) were then conducted using two populations to compare two contrasting land use scenarios from the same location (Pop-1 and Pop-3) out of the original four. In addition, the effect of growing media and seed burial depth on seedling emergence of one population (Pop-1) was also observed. The results indicated that seeds of a population collected from a pasture field (Pop-4) were 75% heavier than the fence line population (Pop-2). Seed length did not vary across populations, but the seed width of a roadside population (Pop-1) was significantly less (37%) than a population from a cropping field (Pop-3). Germination response was same (>90%) in alternating light/dark (14/10 h) or complete dark (24 h) conditions. All populations had >78% germination across a wide range of alternating day/night temperatures (15/5, 25/15, and 35/25°C). Populations did not differ in their germination response to moisture stress. Seeds did not germinate beyond -1.2 MPa water potential, while 50% germination inhibition occurred at -0.67 MPa. Gazania seeds could germinate up to a high salinity level of 300 mM of sodium chloride. Population 1 was more tolerant to salinity than Pop-3 with a 50% reduction in germination occurring at 268 and 252 mM NaCl, respectively. The pH did not affect germination irrespective of the population. Less seeds could emerge from soil (32%) compared to sand (62%) and potting mix (69%). Seedling emergence and root length decreased with increasing burial depth and no emergence was observed at 6 cm depth. However, these results represent a single population tested in burial depth study. Despite some population variations, gazania has flexible germination requirements potentially enabling their invasion.